Relationship Between Integrative Leadership and Performance of Public Boarding Secondary Schools in Selected Counties Under the FCDC Kenya: The Mediating Effect of Employee Motivation - Dahir, Mohamed Abdinoor; Kathula, Domeniter Naomi; Machoka, Paul (Archives of Business Research, 2023)
An integrative leadership framework from an educational perspective is vital in understanding the efforts that are put in by school leaders to support overall school performance. Integrated leadership is also critical in the management and the development of partnerships aimed at increasing the quality of school performance. An integrative kind of leadership motivates members of the school community to maximize their overall performance. Integrative leadership combines the qualities of servant leadership, authentic leadership, and value-based leadership while simultaneously addressing their weaknesses. This paper sought to ascertain the mediating effect of employee motivation on the relationship between integrative leadership and the performance of public boarding secondary schools in selected Counties under the FCDC Kenya. This paper critiqued empirical studies linking the relationship between integrative leadership and performance and the mediating role of employee motivation. This study adopted a pragmatism research philosophy. This study also triangulated data using both qualitative and quantitative methods. The target population included all public boarding secondary schools from four FCDC Counties namely Lamu, Isiolo, Samburu, and Wajir. The study also targeted student leaders, teachers, principals, stakeholders (Board of Management representatives, County, and Teachers Service Commissions (TSC) Directors). The sample included 300 student leaders from 16 public boarding secondary schools in four FCDC Counties. A sample of 96 teachers, 16 principals, 16 Board of Management (BOM) stakeholders, 4 county directors of education and 4 TSC county directors; and 4 representatives of development partners also formed part of the sampling units. Therefore, the total sample size was four hundred and forty (N=440). Questionnaires were used to gather information from the teachers and students while interview guides were used to gather information from the school principals, BOM representatives, and County Directors of education. Interview guides were open-ended and detailed. Data was analysed using both quantitative and qualitative data analysis approaches based on the research objectives. Descriptive statistics was used to summarize quantitative data and the results were presented in frequencies and percentages, while inferential statistics were used to test the study hypothesis. Qualitative data on the other hand was summarized and reported in themes. The study revealed that integrative leadership has a significant relationship with the performance of public boarding secondary schools in selected Counties under FCDC Kenya. Further, the study findings indicated a partial mediating effect on the mediating role of employee motivation on the relationship between integrative leadership and school performance.